The Effect of Risk and Return on Mutual Fund Investment Decisions at Cirebon City Securities - Addin Zainul Adha; Krisdiana; Benny Dhevyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims For study influence risk and return on decision investment mutual funds to investors who invest through company securities in Cirebon City, considering rapid development mutual funds that demand understanding balanced between level risk and potential return in taking decision investment . Research use approach quantitative with type of explanatory research, where primary data is collected through distributed questionnaires​ to 100 mutual fund investors in Cirebon City according to criteria research , then analyzed use Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with help SmartPLS . Measurement model evaluation results show all over indicator has fulfil criteria validity and reliability , while structural model evaluation produce mark coefficient high determination , indicating​ that variables risk and return capabilities explain part big variation decision investment mutual funds . Testing hypothesis prove that risk and return influence positive and significant to decision investment , good in a way partial and simultaneously , so that can concluded that investor perception of risk as well as expected return holding role important in determine decision investment mutual funds , at the same time give contribution theoretical for development study investment and benefits practical for investors as well company securities in push taking decision rational and sustainable investment .​